Clinical and Radiological Outcome of Anterior only Stabilization for AO Type B And C Subaxial Cervical Spine Injury: An Observational Study - Ram Sharma Subedi; Gaurav Raj Dhakal; Bhadra Hamal; Kabita Devi Baral; Badri Rijal; Mahesh Karmacharya; Prem Kumar Sah (Journal of Nepal Medical Association)
Introduction: AO type B and C subaxial cervical spine injuries are highly unstable and require surgical fixation for the stabilization. This study aims to determine their outcome after anterior stabilization clinically and radiologically. Methods: This was an observational cross-section conducted at tertiary level trauma center, from March 2021 to April 2022 after ethical approval from Institutional Review Board (Reference Number: 665/2077/78). Total sampling was done. Cervical spine injuries AO type B and C operated with anterior cervical stabilization were included. Descriptive statistics were used to analyze data. Results: There were 21 cervical spine injuries operated with anterior cervical stabilization during the study period. Among the operated patients 14 (66.67%) were male and 7 (33.33%) were female with the median age of 40 (IQR: 32-51 years). Eleven (52.38%) patients sustained AO type B injury and 10 (47.61%) AO type C injury. The mode of injury was fall from height 14 (66.66%) followed by road traffic accident 6 (28.57%), and physical assault 1 (4.76%). Postoperatively there was 33% improvement in incomplete neurology by one grade on ASIA neurology. Pain was evaluated using Visual Analogue Score and disability was evaluated using Neck disability Index scoring with the median value of 2 (IQR: 0.4-3) and 10 (IQR: 3-13) respectively. Radiographic failure was present in 2 (9.52%) patients. Forteen (66.66%) patients showed Grade 1 fusion, six (28.57%) patients showed Grade 2 fusion, and one (4.76%) patients showed Grade 3 fusion. Conclusions: Almost half of the injuries occurred at the level of C4-C5. Most of the patients had fusion with no new neurological detonation postoperatively.